Enhancement of the two-photon blockade effect via Van der Waals interaction - Hou, Kui; Zhang, Zhendong; Zhu, Chengjie; Yang, Yaping (Frontiers in Physics, 2022)
We theoretically investigate the influence of the Van der Waals interaction on the two photon blockade phenomenon with the corresponding photon correlation functions $g^{(2)}(0)>1$ and $g^{(3)}(0)<1$ in a two atoms cavity-QED system, where two three-level ladder-type atoms are coherently driven by a pumping field and a coupling field simultaneously. Choosing a specific frequency of the coupling field, we show the energy splitting phenomenon caused by the electromagnetically induced transparency. Correspondingly, the two photon blockade phenomenon can be achieved near the two-photon resonant frequency. Using the Van der Waals interaction between the Rydberg states of two atoms, we also show that the two photon blockade can be improved when two atoms radiate in-phase or out-of-phase. As a result, two photons leak from the cavity simultaneously, but the third photon is blockaded. These results presented in this paper hold potential applications in manipulating photon states and generating nonclassical light sources.